Methodical Recommendations for Passing the "Digital World" Topic in 6th Symphony Language Classes - Abdumutalibovna, Maxkamova Guluzroxon (Jurnal Pendidikan Non formal, 2024)
This article describes methodological recommendations for the organization of 6th grade mother tongue lessons from new generation textbooks based on the National Curriculum. This study aims to enhance mother tongue education using modern and interactive methods, tailored to students' characteristics, to foster interest in digital world topics. The methodology employs discussions, oral speeches, and reading comprehension exercises on internet-related terms and digitization and utilize interactive media to engage students in the learning process. The results show successful implementation of contemporary teaching methods, considering students' attributes, achieves the goal of imparting knowledge effectively. Students demonstrate understanding of digital concepts, critical thinking, and vocabulary expansion. Encouraging the use of Uzbek alternatives enhances lexicological skills. The study underscores the importance of adapting teaching approaches to the digital age.